Effectiveness of Social Media-Based STM (Science, Technology, and Society) Learning Model with Case Study Learning Method in Class XI High School Sociology Material - Adibah, Elisa Dourothun Nafis El Adibah; Pristine Adi, Depict; Wicaksono, Syafril; Hadi al Asy’ari, M. Khoirul (Proceeding International Conference on Religion, Science and Education, 2024)
The use of social media in Indonesia has continued to grow significantly in the last decade, with evidence that Indonesia occupies the third position of the largest social media user in the world. This makes social media an inherent part of people’s lives. In the context of education, social media can be an effective tool to enhance learning and adapt to the ever-changing changing world, especially in the 5.0 era which is characterized by technological sophistication and rapid social changes in everyday life. This inspired researchers to examine the effectiveness of the social media-based STM (Science, Technology, and Society) learning model with a case study learning method with a focus on sociology material in Class XI Senior High School. The STM learning model with the case study method has compatibility in the implementation of the learning process by prioritizing problems and linking science concepts with technology products that are developing in society. With a problem-oriented framework, it is ideal for class XI sociology material that addresses social problems in society. So with this, the researcher wants to examine three problem formulations, including: One is why the social media-based STM learning model with the case study learning method was chosen as a learning approach in class XI sociology material. Two, How to implement the social media-based STM learning model with the case study learning method in class XI high school sociology material. Three, how is the effectiveness of applying the STM Model with the case study method in teaching sociology material for class XI?. This research uses a descriptive qualitative approach through the literature study method. The results showed that the social media-based STM learning model with the case study method can increase student motivation and participation, facilitate discussion and collaboration between students, expand access to relevant information, and provide real learning experiences.